Refleksi Teologi Modern Tentang Yesus Kristus Penyelamat - A. Sunarko (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2011)
Abstract: If salvation is understood in the paradigm of deification, what usually becomes the focus of attention of the Jesus event is the incarnation. The divine became man so that human nature might become divine. But if salvation, on the other hand, is understood in the paradigm of satisfaction (satisfactio), the suffering and the death of Jesus on the cross becomes the focus of attention. Human beings are saved because Jesus— through his suffering and death on the cross—has become atonement for the sins of human beings. In the aforementioned paradigms, the rich meaning of Jesus’ life and ministry do not have sufficient place. In modern theology the life and ministry of Jesus have a more central place. Only in this way, can Christian theology respond to the quest of modern human beings for the meaning of life, and give inspiration for the efforts of human beings as subjects to realize themselves. Keywords: Modern, salvation, Jesus event, deification and Jesus’ birth, atonement and cross, life and ministry of Jesus. Abstrak: Bila keselamatan dimengerti dalam paradigma deifikasi (pengilahian), biasanya yang menjadi fokus perhatian dari peristiwa Yesus Kristus adalah natal/inkarnasi. Yang ilahi menjadi manusia sehingga kodrat manusia diilahikan. Bila keselamatan dimengerti dalam paradigma satisfactio/silih, maka terutama sengsara dan wafat Yesus di salib lah yang menjadi pusat perhatian. Manusia diselamatkan, karena Yesus—melalui sengsara dan wafat di salib—telah menjadi silih atas dosa-dosa manusia. Dalam kedua paradigma tersebut kekayaan makna hidup dan karya Yesus Kristus kurang mendapat tempat. Dalam teologi modern hidup dan karya Yesus Kristus hendak diberi tempat yang lebih sentral. Kiranya hanya dengan demikian teologi Kristiani dapat memberi tanggapan atas pencarian manusia modern akan makna kehidupan, dan memberi inspirasi bagi upaya manusia sebagai subjek untuk merealisasikan diri. Kata-kata kunci: Modern, keselamatan, peristiwa Yesus Kristus, deifikasi dan natal, silih dan salib, hidup dan karya Yesus.